PHENOLIC COMPOUNDS FROM LEAVES OF Amensiodendron chinense (Sapindaceae) - Hồ Văn Ban; Vũ Văn Chiên; Nguyễn Thị Huệ; Phạm Thị Hằng; Nguyễn Lê Tuấn; Hoàng Nữ Thùy Liên; Nguyễn Quốc Vương (My University, 2021)
PHENOLIC COMPOUNDS FROM LEAVES OF Amensiodendron chinense (Sapindaceae)
Keywords: Phenolic compounds